Gaussian Pulses over Random Topographies for the Linear Euler Equations - Flamarion, M. V.; Ribeiro-Jr, R. (Trends in Computational and Applied Mathematics, 2024)
This study investigates numerically the interaction between a Gaussian pulse and variable topography using the linear Euler equations. The impact of topography variation on the amplitude and behavior of the wave pulse is examined through numerical simulations and statistical analysis. On one hand, we show that for slowly varying topographies, the incoming pulse almost retains its shape, and little energy is transferred to the small reflected waves. On the other hand, we demonstrate that for rapidly varying topographies, the shape of the pulse is destroyed, which is different from previous studies.